The Enhancing Competency Development of the State Civil Apparatus in the Digital Era: Challenges and Strategies - Dewi, Tiara; Hidayat, Rahmat; Firdaus, F. (Manunggal Halim Jaya, 2025)
This study aims to analyze the design of appropriate strategies for competency development at BKPSDM Sarolangun Regency. The type of research used is qualitative research. The data collection process uses documentation, observation, and interviews. The data analysis technique uses SWOT analysis to identify the strategic model of team member competency development in BKPSDM Sarolangun Regency by analyzing external factors, namely opportunities and threats, and internal factors, namely strengths and weaknesses. The results showed that the total IFE score of 0.74 indicates that BKPSDM Sarolangun Regency has a relatively strong position in utilizing internal factors compared to existing weaknesses. The total EFE score of 0.60 suggests that BKPSDM Sarolangun Regency can use external opportunities to support competency development. These results show a structured strategy, using technology and providing adequate incentives; team member competence is hoped to develop significantly and positively impact performance and public services.